Software solutions in the processes of creating and using atlas interactive maps - Chabaniuk, Viktor S.; Rudenko, Leonid G. (Journal of the Belarusian State University. Geography and Geology, 2019)
Cartographic interactivity is now most often understood as an addition to cartographic representations for end users of electronic maps. The article substantiates the need to extend this understanding. This extension will help in creation of the modern atlas systems, which are increasingly being developed as integrated or consisting of several systems. Along with end users, expert-cartographers (developers) and analysts also become users of atlas systems and their interactive maps. Users with relevant knowledge are combined into epistemologically ordered echelons – the higher the echelon, the more knowledge about interactivity the user should possess. Therefore, atlas interactive cartography should now be considered for many simultaneously operating systems and for many users. Examples of new operations of cartographic interactivity for new echelons of users are given: for expert-cartographers this is a dynamic change (i. e. during the operation of the system) of the cartographic method of modeling actuality, and for analysts, the model itself. A review of software solutions that are used to implement extended cartographic interactivity when creating a new generation of atlas systems has been completed. To prove the results, the methods of new relational cartography are used. In particular, the method of conceptual frameworks of atlas systems is used, which allows combining the methods of classical cartography and the methods of relational cartography into the system method of future system cartography. As examples of the paradigms of classical cartography, the communicative paradigm and growth perspective of R. Roth from the University of Wisconsin-Madison are chosen.